SUN-005 Hirsutism Due to Bilateral Leydig Cell Tumors - Shakir, Mohamed K M (J Endocr Soc, 2020)
Severe hyperandrogenism in post-menopausal women is rare. It may be caused by either benign or malignant neoplasms of the adrenal or ovary. We report a rare case of a post-menopausal woman with hirsutism associated with virilization due to Leydig cell tumors (LCT) of both ovaries. Case report 61 yo female presented for evaluation of hirsutism. She had also been experiencing increased facial hair growth, deepening of voice, clitoromegaly, alopecia, and acne. Physical examination: normal vital signs. Patient had signs of virilization, including coarse hair along her upper lip, chin, lower abdomen and inner thigh with Ferriman-Gallwey score of 8, acne, and clitoromegaly. She had no signs of acanthosis nigricans or Cushing syndrome. Base line labs: Hemoglobin 16.2 gm/dL (ref 12.0 to 15.5), total testosterone 803 ng/dL (ref 3–41), free testosterone 20.2 pg/mL (ref 0.0–4.2), estradiol 77 pg/mL (<6.0−54.7), estrone 148 pg/mL (ref 7–40), FSH 11.5 mIU/mL (ref 25.8 - 134.8), LH 6.90 mIU/mL (ref 7.7 - 58.5), androstenedione 28 ng/dL (ref 17–99), DHEAS 99.9 mcg/dL (ref 19–205), dehydroepiandrosterone 512 ng/dL (ref 31–701), inhibin A 2.3 pg/mL (ref <5), inhibin B <7.0 pg/mL (ref 00-16.9), 17-alpha hydroxyprogesterone 187 ng/dl (ref <51). Her other serum markers such as anti -Mullerian hormone, alpha-fetoprotein, and hCG were normal. A CT scan of adrenals: normal. Similarly a transvaginal US did not show any ovarian pathology, however MRI of the pelvis showed homogeneous ovarian enhancement bilaterally and based on this information a diagnosis of ovarian hyperthecosis was considered and patient underwent laparoscopic bilateral oophorectomy. Pathology confirmed: LCT in both ovaries. Laboratory values performed 3 months later showed the following values: hemoglobin 14.2 gm/dL, total testosterone 13 ng/dL, free testosterone 1.4 pg/mL, LH 124 mIU/mL, FSH 99mIU/mL, estradiol <5.0 pg/mL. In 6 months she had significant improvement in hirsutism and virilization. Discussion Hyperandrogenism, especially serum testosterone in the male range with rapidly progressive hirsutism or virilization signs in a female indicates tumor etiology. Androgen-secreting ovarian tumors are usually small and often embedded in the ovary. Transvaginal US is useful in the diagnosis of ovarian tumors. However, in our case, transvaginal US failed while MRI scan showed bilaterally enlarged ovaries and with this information patient underwent bilateral oophorectomy. Although 5 cases of bilateral LCT are reported in the literature, LCT is unilateral 95% of the time, the pathogenesis of Leydig cell proliferation and LCT is unclear. In conclusion, androgen secreting tumors should be considered in women (especially in post-menopausal state) with hyperandrogenism and hirsutism. In fact, diffuse stromal Leydig cell hyperplasia and small Leydig cell tumors may be missed on imaging and in some cases only pathology can confirm the result.